(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
After a few brief remarks on the life of the entomologist, Giacomo Del Guercio, the complete history of his aphid collection, which today is in the possession of the Institute of Agricultural Entomology of the U niversity of Milan, will be presented. The collection, which consists of about 3,000 slides, although presenting lacunae of various types (for example, for species described as new, specimens for comparison or indications of types are missing) nonetheless contains materiai of noteworthy interest for the study of aphids in Italy. A list of the aphids identified by Del Guercio and one of its host plants will conclude this paper.